An alternative view of finance, saving, deficits, and liquidity - L. Randall Wray (Levy Economics Institute of Bard College, 2009)
This paper contrasts the orthodox approach with an alternative view on finance, saving, deficits, and liquidity. The conventional view on the cause of the current global financial crisis points first to excessive United States trade deficits that are supposed to have 'soaked up' global savings. Worse, this policy was ultimately unsustainable because it was inevitable that lenders would stop the flow of dollars. Problems were compounded by the Federal Reserve's pursuit of a low-interest-rate policy, which involved pumping liquidity into the markets and thereby fueling a real estate boom. Finally, with the world awash in dollars, a run on the dollar caused it to collapse. The Fed (and then the Treasury) had to come to the rescue of U.S. banks, firms, and households. When asset prices plummeted, the financial crisis spread to much of the rest of the world. According to the conventional view, China, as the residual supplier of dollars, now holds the fate of the United States, and possibly the entire world, in its hands. Thus, it's necessary for the United States to begin living within its means, by balancing its current account and (eventually) eliminating its budget deficit. I challenge every aspect of this interpretation. Our nation operates with a sovereign currency, one that is issued by a sovereign government that operates with a flexible exchange rate. As such, the government does not really borrow, nor can foreigners be the source of dollars. Rather, it is the U.S. current account deficit that supplies the net dollar saving to the rest of the world, and the federal government budget deficit that supplies the net dollar saving to the nongovernment sector. Further, saving is never a source of finance; rather, private lending creates bank deposits to finance spending that generates income. Some of this income can be saved, so the second part of the saving decision concerns the form in which savings might be held-as liquid or illiquid assets. U.S. current account deficits and federal budget deficits are sustainable, so the United States does not need to adopt austerity, nor does it need to look to the rest of the world for salvation. Rather, it needs to look to domestic fiscal stimulus strategies to resolve the crisis, and to a larger future role for government in helping to stabilize the economy.
Keywords: E12; E21; E22; E42; E63; F32; 330; finance; saving; budget deficits; current account deficits; financial crisis